Human Milk Oligosaccharides Differ between HIV-Infected and HIV-Uninfected Mothers and Are Related to Necrotizing Enterocolitis Incidence in Their Preterm Very-Low-Birth-Weight Infants. Issue 8 (11th June 2014) - Van Niekerk, Evette; Autran, Chloe A.; Nel, Daniel G.; Kirsten, Gert F.; Blaauw, Reneé; Bode, Lars
Abstract: The heavy burden of maternal HIV infection has resulted in a high prevalence of premature birth and associated necrotizing enterocolitis (NEC). Human milk oligosaccharides (HMOs) were recently associated with HIV infection and transmission through breastfeeding and were also shown to reduce NEC in an animal model, particularly the HMO disialyllacto-N-tetraose (DSLNT). The primary aim of this study was to verify differences in HMO composition between HIV-infected and HIV-uninfected women. The secondary aim was to assess whether the HMO composition in the milk of mothers whose infants were diagnosed with NEC differs from that of mothers whose infants did not develop NEC. This study forms part of a larger clinical trial conducted at the Tygerberg Children's Hospital, Cape Town, South Africa, which recruited HIV-infected and HIV-uninfected mothers and their preterm infants (<34 wk gestation; ≥500 and ≤1250 g). Eighty-two mother-infant pairs were selected for the substudy. Mother-infant pairs were stratified according to the mother's HIV (infected/uninfected) and secretor status (secretor/nonsecretor). HMOs in 4- and 28-d postpartum milk samples were analyzed by HPLC and compared between groups. Our results confirm previous reports that HIV-infected mothers have higher relative abundances of 3′-sialyllactose in their milk compared with HIV-uninfected mothers (10.7% vs. 6.8%; P < 0.01). Most intriguingly, the data also indicated that low concentrations of DSLNT in the 4-d milk samples in the mother's milk increased the infant's risk of NEC (200 ± 126 vs. 345 ± 186 μg/mL; P < 0.05), which is in accordance with results from previously published animal studies and warrants further investigation. This trial was registered at clinicaltrials.gov as NCT01868737.